Under the chest pain center mechanism, whether the nursing handover affects the nursing efficiency and the outcomes of patients with STEMI in the emergency department? A retrospective study - Zhenyu Luo; Sihui Liu; Yunying Li; Shuyan Zhong (BMC Emergency Medicine, 2023)
Abstract Background The introduction of chest pain centers (CPC) in China has achieved great success in shortening the duration of nursing operations to significantly improve the treatment and outcomes of patients with ST-segment elevation myocardial infarction (STEMI). The nursing handover period is still considered the high incidence period of adverse events because of the distractibility of nurses’ attention, potential interruption, and unclear responsibilities. Under the CPC mechanism, the nursing efficiency and patients’ outcome, whether affected by the nursing handover, is still a knowledge gap in research. This is also the aim of this study. Methods A retrospective study was conducted with data from STEMI patients from a tertiary hospital in the north of Sichuan Province from January 2018 to December 2019 through the Chinese CPC database. Patients are divided into handover and non-handover groups according to the time they presented in the Emergency Department. D2FMC, FMC2FE, FMC2BS, FMC2CBR, FMC2FAD, and D2W were selected to measure nursing efficiency. The occurrence of major adverse cardiovascular events, the highest troponin values within 72 h of hospitalization, and the length of hospitalization were selected to measure the patient outcomes. Continuous variables are summarized as mean ± SD, and t-tests of the data were performed. P-values < 0.05 (two-tailed) were considered statistically significant. Results A total of 231 cases were enrolled, of which 40 patients (17.3%) were divided into the handover period group, and 191 (82.6%) belonged to the non-handover period group. The results showed that the handover period group took significantly longer on items FMC2BS (P < 0.001) and FMC2FAD (P < 0.001). Still, there were no significant differences in D2FMC and FMC2FE, and others varied too little to be clinically meaningful, as well as the outcomes of patients. Conclusion This study confirms that nursing handover impacts the nursing efficiency of STEMI patients, especially in FMC2BS and FMC2FAD. Hospitals should also reform the nursing handover rules after the construction of CPC and enhance the triage training of nurses to assure nursing efficiency so that CPC can play a better role.